DEVELOPMENT OF A PROTOTYPE OF A HYDROELECTRIC POWER PLANT BASED ON BOYLE'S FLASK AS A SCIENCE TEACHING MATERIAL - hari mukti, wiji aziiz; kurniawan; Esti Wahyu Kurniawati (Mataram University, 2024)
Abstract: Boyle's flask is an innovation by scientist Robert Boyle which utilizes gravity and water which can move continuously without external energy, but the results of his research have not yet been used to become a prototype for a power plant even though in theory it already meets the criteria to become a prototype for a power plant. This research aims to determine the design and development of a Boyle's flask-based hydroelectric generator prototype as science teaching material and to measure the amount of output power produced from the Boyle's flask-based hydroelectric generator prototype. The method used is development using the ADDIE model. The results of this research are: the design of a Boyle's flask-based hydroelectric power plant prototype as science teaching material and the magnitude of the electric current produced from the Boyle's flask-based hydroelectric power plant prototype and an analysis of the relationship between the size of the Boyle's flask-based hydroelectric power plant prototype. flask with a strong electric current that is produced cannot be done because liquid substances, namely water and salt water, cannot flow endlessly even though there have been changes in several variables (using 2.5 inch and 0.25 inch hoses, using water and salt water which have different densities).